(untitled) (Research, Society and Development, 2022)
The aim of this article is to propose a reflection on the human being himself, who is called to collaborate with God in taking care and cultivating the creation. The question is presented: what enables the person to be a collaborator of God? It is a narrative construction, for which the two fundamental nucleus of data, texts and information were the Social Doctrine of the Church and the documents of the Magisterium that elucidate the project, experience and family dynamics. The narrative presents that the person, in alliance with the Creator, becomes the administrative act of God in the world, then elucidates the ’administrative essence’, the first gift with which God addresses the human being in the call/sent to care and cultivate the garden. The person is raised as God’s administrative act in the world, fostering that it is in the family that the children/Ben of God must care for the earth and to become the nation of the children/people of God, a nation without geographical limitations, based on love and trust in the Kingdom of God that is made in the contingency of creation under human administration.